2014
DOI: 10.1002/ijc.28930
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index at early adulthood, subsequent weight change and cancer incidence and mortality

Abstract: Obesity later in adulthood is associated with increased risks of many cancers. However, the effect of body fatness in early adulthood, and change in weight from early to later adulthood on cancer risk later in life is less clear. We used data from 13,901 people aged 45-64 in the Atherosclerosis Risk in Communities cohort who at baseline (1987-1989) self-reported their weight at the age of 25 and had weight and height measured. Incident cancers were identified through 2006 and cancer deaths were ascertained thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 36 publications
6
67
0
1
Order By: Relevance
“…For weight gain since early adulthood, consistent with previous studies,(4, 68, 10, 11, 15) we found a positive association with CRC risk and the association was stronger in men than in women. Although it is possible that the older ages of men compared to women at cohort enrollment contribute to the larger elevation of CRC risk associated with weight gain, we did not find strong evidence that the association between weight change and CRC risk varied by age at baseline in either men or women (Supplementary Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For weight gain since early adulthood, consistent with previous studies,(4, 68, 10, 11, 15) we found a positive association with CRC risk and the association was stronger in men than in women. Although it is possible that the older ages of men compared to women at cohort enrollment contribute to the larger elevation of CRC risk associated with weight gain, we did not find strong evidence that the association between weight change and CRC risk varied by age at baseline in either men or women (Supplementary Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the influence of non-surgical weight loss on CRC remains inconclusive in prospective cohort studies, in which weight loss was typically considered only in a single category due to the small number of cases. (4, 610, 15, 33) To our knowledge, our findings provide the first population-based evidence that weight loss during adulthood may be associated with lower risk of CRC.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…(36) We found that an increased weight change trajectory during adulthood was associated with elevated risk of all cancers combined, breast cancer, particularly postmenopausal breast cancer, endometrial cancer, and possibly liver cancer and lymphatic and hematopoietic malignancy, independent of BMI at age 20 and other established risk factors. These results suggest that regardless of BMI at early adulthood, being obese in later life or gaining weight along the way increases the risk of several cancers, emphasizing the importance of maintaining a healthy weight during adulthood.…”
Section: Discussionmentioning
confidence: 80%
“…Johnson et al [7] performed a meta-analysis including 23 studies evaluating BMI and CRC risk finding that for every 8 kg/m2 increase in BMI, the risk of cancer increased by 10%. Even obesity during childhood or adolescence can increase the risk, though the data is less clear due to the significant potential for recall bias [28,29]. Subjects with metabolic syndrome, which includes obesity, diabetes, and pulmonary disease, are at a higher risk for advanced neoplasms found during colonoscopy [30].…”
Section: Inflammatory Bowel Disease (Ibd) Either Ulcerative Colitis Ormentioning
confidence: 99%